Energy Storage in Metallic Glasses via Flash Annealing. (16th October 2018) - Küchemann, Stefan; Derlet, Peter M.; Liu, Chaoyang; Rosenthal, Daniel; Sparks, Gregory; Larson, William S.; Maaß, Robert
Abstract: When the temperature rises in a kinetically frozen and out‐of‐equilibrium system, such as a structural glass, thermal activation usually drives a relaxation to a lower enthalpy state. This is the essence of the ubiquitous thermal ageing of glassy materials below the glass transition temperature. Here, it is shown that an ultrafast temperature rise without subsequent quenching can elevate the system to a higher enthalpy state, thereby erasing the relaxation history. The key of this temperature‐driven rejuvenation is a fast‐heating rate (flash annealing) that brings the glass into a temperature regime above the glass transition within less than a millisecond. Here, the structure is entropically driven towards the liquid state, lowering its free energy, but raising its enthalpy. Subsequent cooling freezes the increased enthalpy before the liquid state is reached, thereby leading to a global energy storage. This ultrafast rejuvenation process is demonstrated for a Zr‐based metallic glass, combining calorimetry, fast in‐situ X‐ray diffraction, and atomistic simulations, showing a tenfold increase in stored enthalpy via flash annealing. Abstract : In this article, it is shown how to erase an aging history of a structural glass via a sub‐millisecond flash‐annealing process. Specifically, a metallic glass is rejuvenated via ultrafast heating to a temperature above the glass transition, without the need of any subsequent quenching method.